OPTIMALISASI STRATEGI PEMASARAN DENGAN PLATFORM SHOPEE PADA PELAKU USAHA DESA GALANG PENGAMPON, PEKALONGAN, JAWA TENGAH - Novianti, Dirasti; Muasomah; Saputro, Kuntoro Agus; Isro, Angfi Akhyanul; Navila, Ayu; Fillah, Ayyuma (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
In this research there is a discussion of marketing strategies on the Shopee platform and the impact of e-commerce on marketing, underlining the important role of marketing strategies in influencing consumer purchasing decisions. Various strategies recommended include optimizing shop profiles, using Shopee features, SEO, collaborating with influencers, marketing with Shopee Ads, data analysis, good customer service, promotions, professional delivery, and participation in Shopee events. Apart from that, this article is the result of the Digital Marketing Seminar held by Kuliah Kerja Nyata (Field Work Lectures) 57 UIN K.H. Abdurrahman Wahid Pekalongan in Galang Pengampon Village, Pekalongan, Central Java. This activity uses seminar and outreach methods to increase understanding of digital marketing, especially on the Shopee e-commerce platform. This activity was carried out to support Micro, Small and Medium Enterprises (MSMEs/UMKM) by involving resource persons experienced in marketing to provide practical guidance for business actors.